THE IMPLEMENTATION OF EVERYDAY PHYSICAL EDUCATION AMONG UPPER PRIMARY PUPILS IN THE NORTH GRATE PLAIN - Gábor FINTOR (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2017)
Regarding physical education, significant changes could be detected in the educational policy with the introduction of the everyday physical education in Hungary. Thus the investigation of alteration in the field of Physical education and sport provides the main topic. Firstly, the appreciation of the fact was measured; on the other hand, we were searching the answer how the positive and negative attitudes toward everyday physical education appeared among the students (N=1153), concerning the aims of the National Curriculum 2012. Results show that the outstanding part of the students (95%) like PE lessons. Regarding gender differences in the appreciation, a significant difference can be pointed out as it is remarkably higher among boys (p=0,000). The role of PE teachers and their motivating effect can be seen in our study.